De qui au juste Nicétas est-il le débiteur?: Une recherche sur les sources et la valeur archéologique de la Synopse de Nicétas Seidès - Danezan, Meredith (Byzantion, 2024)
This article sets out to elucidate the sources that Nicetas Seides consulted when he composed his Synopsis of Holy Scripture in the 12th century, and the way in which he used them. Although it can be considered as ‘recent’, Nicetas’ work reflects the existence of an ancient compilation of argumenta prefacing the Bible, the Synopsis of Pseudo-Athanasius, which Nicetas accessed through a variety of documentary sources (a systematic corpus, prefaces in biblical copies and exegetical catenae).